Two-period price competition of second-hand product platforms with or without blockchain under different supply and demand levels. (April 2023) - Guo, Qiang; Zhao, Pengfei; Cheng, Shengyan; Ahmed, Mansoora
Highlights: The Matthew effect of whether or not to use blockchain is evident. The platform without blockchain is not always a loser. Blockchain and conversion benefits have different effects on different platforms. Abstract: Consumers who buy products from second-hand platforms are troubled because they cannot observe the real quality. Moreover, the absence of after-sales service and no-hassle return policies also lead to the moral hazard of platforms. We introduce blockchain as a quality disclosure technology. Consider two periods of price competition between two platforms with or without blockchain at different supply and demand levels. We find the Matthew effect of whether or not to use blockchain is evident, with the pros and cons accumulating over time. However, the platform without blockchain is not always a loser, even if it is just a follower or myopic decision-maker, related to critical factors such as supply and demand level, platform differentiation, the strength of network effects. In addition, blockchain benefits (quality disclosure perceived by consumers) and conversion benefits (platform options perceived by individual suppliers) contribute positively to the market equilibrium amounts of the blockchain platform in most supply and demand scenarios but are uncertain for the normal platform.